Perbandingan mekanisme pengaturan suhu tubuh mencit (mus musculus l.) Dan katak (amfibi) pada kondisi suhu yang berbeda - Fitriyah, Izza Nailatul (Maliki Interdisciplinary Journal, 2025)
Body temperature is one of the vital indicators controlled by the body. Internal temperature stability is very important to ensure enzymes function optimally, support metabolism, and maintain various other physiological processes. Thermoregulation is a process that involves homeostatic mechanisms to maintain body temperature within the normal range. This is achieved by balancing heat production in the body with heat release to the environment. This research aims to compare the mechanisms for regulating body temperature in mice and frogs under different environmental temperature conditions. This research uses experimental methods. The results of the research show that mice are thermoregulatory animals, which means they can regulate internal body temperature, while frogs are thermoconformer animals, which means they cannot regulate internal body temperature but can change their behavior.